2011
DOI: 10.1113/jphysiol.2011.207548
|View full text |Cite
|
Sign up to set email alerts
|

KCa3.1 channels facilitate K+ secretion or Na+ absorption depending on apical or basolateral P2Y receptor stimulation

Abstract: Non-technical summary The epithelial cells lining the ducts of the human mammary gland are responsible for modifying sodium and potassium concentrations in milk by actively absorbing sodium from and secreting potassium into the ductal fluid. In the present study we show that adenosine triphosphate (ATP) and uridine triphosphate (UTP) can stimulate sodium absorption and potassium secretion by a mechanism that involves increasing intracellular calcium and activation of calcium-dependent potassium channels. We di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
18
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(20 citation statements)
references
References 48 publications
2
18
0
Order By: Relevance
“…Therefore, some of these properties appeared to be similar to those reported for cloned K Ca 3.1 (5,13,15). A K Ca 3.1-like, Ca 2ϩ -activated K ϩ channel has been also shown to be present in both the basolateral and apical membranes of an immortalized cell line derived from human mammary epithelial cells (21,31), which are supposed to have properties of ductal epithelial cell (21). Nevertheless, it remains unknown whether other types of K ϩ channel are expressed in mammary epithelial cells.…”
supporting
confidence: 69%
See 1 more Smart Citation
“…Therefore, some of these properties appeared to be similar to those reported for cloned K Ca 3.1 (5,13,15). A K Ca 3.1-like, Ca 2ϩ -activated K ϩ channel has been also shown to be present in both the basolateral and apical membranes of an immortalized cell line derived from human mammary epithelial cells (21,31), which are supposed to have properties of ductal epithelial cell (21). Nevertheless, it remains unknown whether other types of K ϩ channel are expressed in mammary epithelial cells.…”
supporting
confidence: 69%
“…Therefore, K ϩ channels at the basolateral membranes of MS cells would not only mediate a pathway, through which K ions transported into the cells by the Na ϩ -K ϩ -ATPase and Na ϩ -K ϩ -2Cl Ϫ symporter are recycled, but would also hyperpolarize the membrane potential to provide the driving force for the apical Cl Ϫ efflux into the lumen. Likewise, K ϩ channels in the apical membrane would be supportive for apical Cl Ϫ secretion and for apical K ϩ secretion and Na ϩ absorption that might occur in mammary epithelial cells (3,31). In line with these potential roles of K ϩ channels, previous patch-clamp studies have identified a Ca 2ϩactivated K ϩ current in mouse mammary secretory epithelial cells (of acinar cell origin) in primary culture (6,8).…”
mentioning
confidence: 85%
“…ATP acts synergistically with oxytocin to increase intracellular Ca 2+ in mouse mammary myoepithelial cells (Nakano et al 2001). P2Y 2 receptors appear to be involved (Blaug et al 2003;Palmer et al 2011). It is not clear whether the source of ATP is neural or paracrine.…”
Section: Sweat Glandsmentioning
confidence: 96%
“…In the human mammary epithelial cell line 31EG4, P2Y 2 receptors mediate apical Ca 2+ -dependent Cl − and fluid secretion (Blaug et al, 2003). In immortalized human mammary epithelial cells activation of P2Y 2 receptors induces Ca 2+ -dependent K + secretion in the apical membrane of the cells, and Na + absorption in the basolateral membrane (Palmer et al, 2011). In bovine mammary epithelial cells ATP increased Ca 2+ -mediated H + efflux; pre-treatment with the lactogenic hormones prolactin, dexamethasone and insulin attenuated the ATP-induced Ca 2+ i increase and the increases in H + efflux (Katoh et al, 2001).…”
Section: Breasts and Mammary Glandsmentioning
confidence: 99%